Sistem Pengaduan Kelurahan untuk Peningkatan Pelayanan Masyarakat - Nurrohman, Hafidz Atsal; Dewi, Nandita Sekar Sukma; Ramadhan, Taufiq Fadhly (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Development of a sub-district complaint system as a participatory mechanism in improving public services at the local level. This system aims to provide a forum for the community to submit complaints regarding sub-district issues, ranging from infrastructure to security. Through a complaint form that is easily accessible through various channels, such as mobile applications and websites, the public can quickly and efficiently convey the problems they are experiencing. Incoming complaints are classified and prioritized based on type and level of urgency, enabling sub-district governments to respond effectively. This system is also integrated with local government structures, and has good coordination in handling complaints. Transparency is a key focus, with information about complaints, their status and actions taken available for the public to access.